Uji Keterawetan Kayu Karet (Hevea Brasiliensi Muell. Arg) Menggunakan Bahan Pengawet Biocide - Pangestu, Hizbulah; Fakhri, Fakhri; Kamaldi, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Rubber wood (Hevea brasiliensis, Muell Arg) belongs to the Euphorbiaceae family. Rubber wood is susceptible to fungal attack, especially blue fungus (blue stain). The use of wood preservatives is the most effective way to improve the quality of wood. wood preservation is an understanding that talks about the amount of preservative that seeps into wood. This study aims to determine the durability of rubber wood by three of absorption, retention and penetration. The research method was carried out by cold immersion with a preservative used was Biocide-TCMBT / MBT with a dosage of preservative used 0,25%, 0,50%, 0,75% and 1% of water, with a number of sample repetitions five times with. The results of the absorption test that have been carried out the absorption value of immersion for 36 hours have a higher value than the absorption value of immersion for 5 minutes, 12 hours and 24 hours in all variations of the dosage of preservatives. The results of retention testing that have been carried out show that the retention value of rubber wood samples with a preservative dose of 0,25 %, 0,50 %, 0,75 % and 1% does not meet the retention standard, namely: 8kg / m³ (SNI 03-5010.1, 1999). The results of the penetration test that have been carried out show that the penetration value of rubber wood samples with a preservative dose of 0,25 %, 0,50 %, 0,75 % and 1% does not meet the penetration standard, namely: 5mm (SNI 03-5010.1, 1999). Keywords: Rubber Wood, Biocide, Absorption, Retention, Penetration